Sources of macroeconomic fluctuations in Malaysia: an empirical test of the Keynesian model - Abdul Manap, Turkhan Ali; Kassim, Salina (Curtin University of Technology, Perth, Australia and Ryukoku University, Kyoto, Japan., 2007)
Identifying the sources of macroeconomic fluctuations is critical to formulating macroeconomic policies. This paper investigates the sources of macroeconomic fluctuations in Malaysia based on the traditional Keynesian framework, using both the standard VAR and structural VAR methods. The joint behavior of the key macroeconomic variables in Malaysia is shown to be consistent with the dynamic transmission of demand and supply shocks through the mechanisms described in the Keynesian model. Positive supply shocks increase output while negative supply shocks contract output and increase price level. Money supply shocks stimulate output and increase the price level. These results are further supported by a variance decomposition analysis